Case Report: Pazopanib-induced acute coronary syndrome - Yadalam, Adithya K.; Schultz, William M.; Han, Chanhee; Mandawat, Anant (Frontiers in Cardiovascular Medicine, 2024)
Introduction Pazopanib is a tyrosine kinase inhibitor approved for the treatment of metastatic renal cell carcinoma and advanced soft-tissue sarcoma that functions by inhibiting vascular endothelial growth factor receptors. Although the package insert and current cardio-oncology guidelines indicate a risk of acute coronary syndrome (ACS) associated with pazopanib, the causative role of pazopanib in arterial thrombosis is unclear, due to a lack of focused coronary disease evaluation in oncology clinical trials prior to pazopanib initiation. Herein we present a patient on pazopanib with an antecedent ischemic evaluation to demonstrate the first reported case of ACS directly attributable to pazopanib. Case Description A 65-year-old woman with metastatic leiomyosarcoma presented to the hospital with ACS. Pazopanib had been initiated 8 months prior, and ischemic evaluation 6 weeks prior to hospitalization demonstrated mild CAD. Emergent cardiac catheterization revealed a large thrombotic occlusion of the mid-left anterior descending coronary artery involving the secondary diagonal artery, which was treated with manual aspiration thrombectomy. Pazopanib was discontinued, and the patient was discharged from the hospital twelve days later. Discussion Although pazopanib is associated with ACS, there is a lack of definitive data supporting this association. This case-based demonstration of pazopanib-induced ACS provides a discrete clinical example of this phenomenon. The patient’s minimal atherosclerotic burden 6 weeks prior to her presentation for ACS strongly suggests causality attributable to pazopanib. Given the increased risk for ischemic heart disease, careful attention and an individualized risk assessment for coronary artery disease should be provided to patients who are prescribed pazopanib.